A comparative study on thermally and laser annealed copper and silver doped CdTe thin film solar cells - Aris K.A.; Rahman K.S.; Ali A.M.; Bais B.; Yahya I.B.; Akhtaruzzaman M.; Misran H.; Abdullah S.F.; Alghoul M.A.; Amin N. (Elsevier Ltd, 2023)
Annealing; Cadmium telluride; Capacitance; Chlorine compounds; Copper compounds; II-VI semiconductors; Neodymium lasers; Pulsed lasers; Semiconductor doping; Silver compounds; Solar cells; Thin film solar cells; Thin films; Yttrium aluminum garnet; Acceptor concentrations; Capacitance voltage measurements; CdTe; Close spaced sublimation; Concentration ranges; Electrical performance; Laser annealing; Solution concentration; Nitrogen compounds; annealing; comparative study; concentration (composition); copper; film; fuel cell; optimization; performance assessment; polymer; silver